The concept of the document in Forensic science - V. S. Sezonov (Law and Safety)
Forensics as a science and sphere of practical activity cannot exist without a document, which is at the same time the main subject of forensic research, a carrier and a means of recording legal information. A document in Forensics is a basic, ambiguous, generalized concept, the definition and classification of which is not unanimous. The tasks of forensic documentation are: 1) development of forensic classification of documents, which will be based on various criteria; 2) development of methods for detecting the subject of forgery; 3) development of methods for rebuilding the information content of the document or its holder. The tasks of forensic classification of documents depend on the development of forensic properties of all types of modern documents. The study of forensic properties of documents is urgent, as the emergence of new types of documents, including electronic, requires an expansion of the list of documents that are involved in examinations. A document in Forensics is defined as a material object with information recorded on it, which is important for establishing the circumstances of criminal proceedings. The problem of using an electronic document as a source of evidence in criminal proceedings is analyzed in detail from the standpoint of the theory of criminal proceedings and forensic science. An electronic document as a source of judicial evidence is an object that carries information that is important for establishing the circumstances to be proved in criminal proceedings, and exists only in the electronic environment in a form acceptable for use in criminal proceedings. Electronic documents can act as a means of committing crimes in the field of computer information, as well as other crimes using computer technology, can be the object of criminal encroachment or information “traces” that arise during the preparation for crime and commission of criminal acts. A cryptocurrency is added to the subject of forensic research, which is essentially an electronic document, an object of civil rights, has value, turnover, place of storage and owner.